Desempenho e avaliação de impacto legislativo na Assembleia Legislativa do estado de Goiás (2014-2019) - Lopes, Victor Hugo Gomes (2020)
Objective: to promote parliamentary performance analysis based on the processing of legislative proposals and the identification of criteria for assessing legislative impact. Methods and techniques: legal-sociological study, based on a hypothetical-deductive method, build on an author database formed by the documentary analysis of 5,255 proposals submitted to the Legislative Assembly of Goiás between 2014 and 2019. Results: prevalence was observed conversion into law of proposals for initiatives by the Executive Branch and other bodies in relation to those originated by parliament. There is a growing increase in the number of bills of parliamentary origin that deal with public policies in recent years. Although not mandatory, it was noted that the presence of criteria for assessing legislative impact tends to increase the chances of the proposal becoming law. Conclusion: the behavior of the state parliament is similar to what the literature observes in the National Congress. The inclusion of AIL as a mandatory step in the legislative process has the potential to reduce the number of symbolic laws and improve the quality of legal normative acts.